INFLUENCE OF ABSORBER LAYER GRADUAL GAP PROFILE ON Cu2ZnSn(S1-Y SeY )4 SOLAR CELL EFFICIENCY: NUMERICAL STUDY - Messei, N (university of el oued/جامعة الوادي, 2021)
The gradual substitution of sulfur atoms (S) by selenium atoms (Se) in Cu2ZnSn(S1-y Sey )4 compounds causes a linear increase in the optical band-gap. For this reason, those compounds are suitable to implement band-gap engineering in compositionally graded solar cells. In this paper, we have worked to take advantage of this feature to enhance the performances of the basic uniform Kesterite and Stannite CZTS1–ySey solar cells. The influence of Tow grading profile was investigated: fully graded (a) and double graded (b). Fully graded Cell showed better parameters than compositionally uniform cells. In Double graded cells it appeared that front grading had a disruptive effect on solar cell parameters. In contrary back grading ameliorates significantly all cell parameters. As a result, the efficiency of kesterite and stannite cells was enhanced from 9.05 and 5.22% to 16.65 and 15.77 % respectively
Article
Keywords: CZTS1–ySey; Kesterite; Stannite; thin film; solar cell; graded; SCAPS 1D.